New records of rare deep‐sea fishes (Teleostei) collected from off north‐eastern Brazil, including seamounts and islands of the Fernando de Noronha Ridge. Issue 4 (25th July 2022) - Mincarone, Michael Maia; Eduardo, Leandro Nolé; Di Dario, Fabio; Frédou, Thierry; Bertrand, Arnaud; Lucena‐Frédou, Flávia
Abstract: Here we report on new data on the occurrence and distribution of rare deep‐sea fishes (Teleostei) collected from off north‐eastern Brazil, including seamounts and oceanic islands of the Fernando de Noronha Ridge (Rocas Atoll and Fernando de Noronha Archipelago). Collections were made by the French RV Antea during the ABRACOS (Acoustics along the BRAzilian COaSt) expeditions between 29 September and 21 October 2015, and 9 April and 10 May 2017. Occurrences of Photostylus pycnopterus (Alepocephalidae), Gigantura chuni (Giganturidae), Ahliesaurus berryi (Notosudidae), Benthalbella infans, Rosenblattichthys hubbsi, Scopelarchoides danae (Scopelarchidae), Scopelengys tristis (Neoscopelidae), Zu cristatus (Trachipteridae), Stylephorus chordatus (Stylephoridae) and Pseudoscopelus cordilluminatus (Chiasmodontidae) are reported for the first time or confirmed in the Brazilian Exclusive Economic Zone. Photostylus pycnopterus and G. chuni are also recorded for the first time in the western South Atlantic, whereas records of P. cordilluminatus are the first in the western Atlantic. Other records of rare species of those families are also reported and discussed.